If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(w + -2) = 2w + -40 Reorder the terms: -7(-2 + w) = 2w + -40 (-2 * -7 + w * -7) = 2w + -40 (14 + -7w) = 2w + -40 Reorder the terms: 14 + -7w = -40 + 2w Solving 14 + -7w = -40 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 14 + -7w + -2w = -40 + 2w + -2w Combine like terms: -7w + -2w = -9w 14 + -9w = -40 + 2w + -2w Combine like terms: 2w + -2w = 0 14 + -9w = -40 + 0 14 + -9w = -40 Add '-14' to each side of the equation. 14 + -14 + -9w = -40 + -14 Combine like terms: 14 + -14 = 0 0 + -9w = -40 + -14 -9w = -40 + -14 Combine like terms: -40 + -14 = -54 -9w = -54 Divide each side by '-9'. w = 6 Simplifying w = 6
| l=8-11+5 | | 3(3x+3)=18 | | 224=x+4(-7x+2) | | 5ln(x+6)-9lnx=0 | | 1/4(8-4p)=2p=12 | | W=l-(A/2) | | -[3-2(X-2)-3(X+1)]=6 | | -2[3(x-1)-2(4x+3)]-3(x-1)=5-[3(2x-1)-4(5x+3)] | | 2x/7=2^2 | | x+(x+15)=55 | | -2[2+5(X+1)+(x-1)]=6 | | 2(2x-5)=3x+x-2x | | 2(x+9)-2(9+x)+x=0 | | -6/7=x/84 | | 32x-6=6 | | x=-7+(5) | | 3(2x+2)-5(2-2x)=x+11 | | 3(w+4)+2(w+3)=108 | | -2.3=1/2y | | 18=1/3 | | 7(2x-3)-(4x+2)=5x-3(4x+5) | | 6z+2(3-z)+5=6z-1 | | 3(s+1)-(5-2)=225 | | 4+(8x-7)=11+7x | | 17p-26=56 | | 7y+5=(-23) | | 15x-8=14x+14 | | 3x^3+21x^2-24x=0 | | 2x+16=x-10 | | 2^-8/2^4 | | 2^-8/a^4 | | 3(2+3x+6x)+5(5x+4)=546 |